Differences in Root Structure of Astragalus membranaceus from Different Geographical Provenances and Their Correlation Analysis with Habitat Factors - Qingsong WU; Haijun XU; Xiaofei WANG; Guanpeng ZHANG; Yueming WANG; Xingyu LIU; Xinran ZHENG; Ming HU; Shurui WANG (Guangdong nongye kexue)
【Objective】To clarify the morphological characteristics and geographic variation patterns of Astragalus membranaceus root systems in Heilongjiang Province, and to elucidate the relationship between their structural differences and habitat conditions.【Method】Using perennial roots of A. membranaceus from 12 geographic provenances in Heilongjiang Province, a comparative anatomical study was conducted. Concurrently, climatic and soil chemical indicators of their habitats were measured.【Result】Significant variations were observed in the root anatomical structures of A. membranaceus across different geographic provenances. Two distinct morphological types of phloem parenchyma cells, namely round and oval-shaped, were observed. Notably, samples from Huma County, Hanjiayuanzi, and Nancha County (Yichun) showed loosely arranged phloem parenchyma tissue. The tissue had prominent intercellular spaces. Particularly, the provenances from Hanjiayuanzi and the Songling region in the Greater Khingan Mountains exhibited unique fiber tissue enrichment characteristics, with significantly higher phloem fiber density than other geographic populations. Among climatic factors, phellem thickness showed an extremely significant negative correlation with altitude (P < 0.01). The phellem thickness of A. membranaceus in low-altitude areas was 36.33%-97.75% greater than that in medium- and high-altitude areas. Phloem thickness increased significantly with the rise in latitude(P < 0.01). The phloem thickness of A. membranaceus in low-latitude areas was 60.08%-112.56% less than that in medium- and high-latitude areas. Vessel diameter widened with the increase in altitude (P < 0.01). The vessel diameter of A. membranaceus in low-altitude areas was 27.95%-73.79% less than that in medium- and high-altitude areas. Xylem thickness increased with the rise in latitude (P < 0.01).The xylem thickness of A. membranaceus in low-latitude areas was 8.2%-53.78% less than that in medium- and high-latitude areas. Among soil chemical properties, phellem thickness showed a significant negative correlation with available nitrogen content (P < 0.05). The phellem thickness of A. membranaceus in habitats with higher soil nitrogen content was 27.82%-60.33% less than that in habitats with lower nitrogen content. Xylem thickness exhibited an extremely significant positive correlation with available phosphorus content (P < 0.01). The xylem thickness of A. membranaceus in habitats with higher soil phosphorus content was 29.51%-39.39% greater than that in habitats with lower phosphorus content.【Conclusion】The anatomical structure of the root system of A. membranaceus exhibits significant geographical provenance difference characteristics. The cellular structure is synergistically regulated by climatic-soil factors. Through the interactive feedback between anatomical traits and habitat factors, A. membranaceus maintains an adaptive balance in heterogeneous habitats, reflecting its certain capacity to adapt to the environment.